2015
DOI: 10.1159/000439589
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ-Inducible Chemokines Decrease upon Selenomethionine Supplementation in Women with Euthyroid Autoimmune Thyroiditis: Comparison between Two Doses of Selenomethionine (80 or 160 μg) versus Placebo

Abstract: Background: Several studies have suggested that selenium may influence the natural history of autoimmune thyroiditis (AIT). Recently, IFNγ-inducible chemokines (CXCL-9, -10 and -11) were shown to be elevated in AIT patients. Objective: This prospective, randomized, controlled study was conducted to evaluate the effect of two doses of selenomethionine (Semet; 80 or 160 µg/day) versus placebo in euthyroid women with AIT, in terms of reduction of anti-thyroid antibodies, CXCL-9, -10 and -11 and improvement of thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(84 citation statements)
references
References 23 publications
1
80
0
3
Order By: Relevance
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%
“…Half of those who prescribed Se (49%) did it prophylactically to prevent serum TSH increase (49%) or to decrease thyroid antibody levels (39%). However, trials among individuals not receiving levothyroxine (LT 4 ) have not reported these effects [10]. 59% of the respondents advocated use of >100 μg Se daily, without having knowledge of the pretherapy Se levels.…”
Section: Chronic Autoimmune Thyroiditis In Euthyroid Individualsmentioning
confidence: 99%
“…In contrast, a very recent study performed in Italy among patients with normal selenium concentration values has shown that selenium supplementation had no positive effect on thyroid echogenicity or TPOAb levels [22].…”
Section: Rycina 1 Schemat Badaniamentioning
confidence: 79%